Forced Oscillations

Forced oscillations occur when an external periodic force is applied to a system, causing it to oscillate at a frequency other than its natural frequency. This force can be applied in various forms, such as mechanical, electrical, or gravitational forces. Examples include pushing a swing or an electrical oscillator.

Forced oscillations are also known as forced vibrations. When the frequency of the external periodic force matches the natural frequency of the system, resonance occurs, leading to a significant increase in the amplitude of oscillation. This phenomenon is commonly referred to as frequency resonance.

In forced oscillations, the amplitude of oscillation may experience damping, which can decrease the amplitude over time. However, if the external energy supplied to the system matches or exceeds the energy loss due to damping, the amplitude can remain relatively constant.

When a forced oscillation system is subjected to a sudden change in the external force (such as its frequency or amplitude), the system needs some time to adjust to this change and reach a new steady-state behavior. During this adjustment period, the oscillations exhibit transient behavior, characterized by changes in amplitude, phase, and other oscillatory parameters.

The transient effects in forced oscillations typically decay over time as the system approaches its new steady-state behavior. The duration and magnitude of the transient effects depend on various factors such as the system's damping, the nature of the external force, and the initial conditions of the system.

Differential equation of FHO

Forced Oscillations

Consider a body of mass mm oscillating under the action of an external periodic force Fe=F0sinptF_e = F_0sinpt where F0F_0 is the maximum value of this force and pp is angular frequency.

The body also experiences restoring force Fr=kxF_r=-kx where xx is the displacement of body at an instant of time tt and frictional force Fd=rvF_d = -rv where rr - damping constant and v=dxdtv=\frac{dx}{dt} along with the periodic force.

Then, Total force acting on body is:-

F=Fr+Fd+FeF = F_r + F_d + F_e

From Newton's second law, F=ma=md2xdt2F = ma = m\frac{d^2x}{dt^2}

Thus, above equation becomes:-

md2xdt2=kx+rdxdt+F0sinptm\frac{d^2x}{dt^2} = -kx + -r\frac{dx}{dt} + F_0sinpt

On dividing above equation by mm we get,

d2xdt2+kmx+rmdxdt=F0msinpt\frac{d^2x}{dt^2} + \frac{k}{m}x + \frac{r}{m}\frac{dx}{dt} = \frac{F_0}{m}sinpt

On Putting, km=ω2  ,  rm=2b  and  F0m=f0\frac{k}{m} = \omega^2\;,\; \frac{r}{m} = 2b\;\:\text{and}\;\: \frac{F_0}{m}=f_0 we get,

d2xdt2+2bdxdt+ω2x=f0sinpt      —– equation 1\frac{d^2x}{dt^2} + 2b\frac{dx}{dt} + \omega^2x = f_0sinpt \; \; \; \text{----- equation 1}

This is the differential equation for forced harmonic oscillator.

Solution of differential equation of FHO

The complete solution of above differential equation is given by the sum (x)(x) of complementary function (x1)(x_1) and particular integral (x2)(x_2)

i.e. x=x1+x2    —– equation - Ax = x_1 + x_2 \; \; \text{----- equation - A}

  • To find complementary function (x1)(x_1) [Transient State]. Put R.H.S of above differential equation to 0, we get:-

    d2xdt2+2bdxdt+ω2x=0\frac{d^2x}{dt^2} + 2b\frac{dx}{dt} + \omega^2x = 0

    This is the differential equation for damped harmonic oscillator whose solution in case of light damping (b2<ω2)(b^2< \omega^2 ) is given as:-

    x1=aebt[sin(nt+Φ)]x_1 = ae^{-bt}[sin(nt + \Phi)] where, n=ω2b2n=\sqrt{\omega^2 - b^2} represents the frequency of oscillation, and Φ1Φ_1 is the phase angle and a=x0na=\frac{x_0}{n}.

    In above equation the amplitude aebtae^{-bt} decays exponentially with time. The motion therefore after sufficiently long time dies down, so this state is called Transient State.

  • To find Particular Integral (x2)(x_2) [Steady State].

    When the external periodic force is applied on the oscillator, then the driving force tends to make the oscillator to oscillate with frequency of driving force but oscillator itself want to oscillate with its own natural frequency. But after sufficiently long time, transients die down (due to amplitude decaying exponentially with time) and ultimately the oscillator performs oscillations at frequency of driving force. This is called Steady State.

    Let x2=Asin(ptΦ)    —– equation 2x_2 = Asin(pt-\Phi)\; \; \text{----- equation 2} be particular integral of equation 1.

    On differentiating above equation twice, we get:-

    dxdt=Apcos(ptΦ)\frac{dx}{dt} = Apcos(pt-\Phi)

    d2xdt2=Ap2sin(ptΦ)\frac{d^2x}{dt^2} = -Ap^2sin(pt-\Phi)

    Putting these values in equation 1, we get:-

    Ap2sin(ptΦ)+2b[Apcos(ptΦ)]+-Ap^2sin(pt-\Phi) + 2b[Apcos(pt-\Phi)] +

    ω2Asin(ptΦ)=f0sinpt\omega^2Asin(pt-\Phi) = f_0sinpt

    Asin(ptΦ)[ω2p2]+Asin(pt-\Phi)[\omega^2 - p^2] +

    2b[Apcos(ptΦ)]=f0sin((ptΦ)+Φ)2b[Apcos(pt-\Phi)] = f_0sin((pt-\Phi) + \Phi)

    We know, sin(A+B)=sinAcosB+cosAsinBsin(A+B) = sinAcosB + cosAsinB

    Asin(ptΦ)[ω2p2]+Asin(pt-\Phi)[\omega^2 - p^2] +

    2b[Apcos(ptΦ)]=2b[Apcos(pt-\Phi)] =

    f0[sin(ptΦ)cosΦ+cos(ptΦ)sinΦ]f_0[sin(pt-\Phi)cos\Phi + cos(pt-\Phi)sin\Phi]

    Asin(ptΦ)[ω2p2]+Asin(pt-\Phi)[\omega^2 - p^2] +

    2b[Apcos(ptΦ)]=2b[Apcos(pt-\Phi)] =

    f0sin(ptΦ)cosΦ+f0cos(ptΦ)sinΦ f_0sin(pt-\Phi)cos\Phi + f_0cos(pt-\Phi)sin\Phi

    On Equating the coefficient of sin(ptΦ)sin(pt-\Phi) and cos(ptΦ)cos(pt-\Phi) we get,

    A[ω2p2]=f0cosθ    —– equation 3A[\omega^2 - p^2] = f_0cos\theta \; \; \text{----- equation 3}

    2bAp=f0sinΦ    —– equation 42bAp = f_0sin\Phi \; \; \text{----- equation 4}

    On squaring and adding above two equations we get,

    A2[ω2p2]2+4b2A2p2=f02A^2[\omega^2 - p^2]^2 + 4b^2A^2p^2 = f_0^2

    or

    A=f0(ω2p2)2+4b2p2A = \frac{f_0}{\sqrt{(\omega^2 - p^2)^2 + 4b^2p^2}}

    This is the expression for amplitude of forced oscillation.

    Now, to find phase of forced oscillations, divide equation 4 by 3 we get,

    tanϕ=2bpω2p2tan\phi = \frac{2bp}{\omega^2 - p^2}

    The phase difference Φ=tan12bpω2p2\Phi = tan^{-1}\frac{2bp}{\omega^2 - p^2}

    Putting values of AA and Φ\Phi in equation - 2 we get,

    x2=f0(ω2p2)2+4b2p2sin(pttan12bpω2p2)x_2 = \frac{f_0}{\sqrt{(\omega^2 - p^2)^2 + 4b^2p^2}}sin(pt - tan^{-1}\frac{2bp}{\omega^2 - p^2})

Now putting values of x1x_1 and x2x_2 in equation - A we get,

x=aebt[sin(nt+Φ)]+x = ae^{-bt}[sin(nt + \Phi)] +

f0(ω2p2)2+4b2p2sin(pttan12bpω2p2) \frac{f_0}{\sqrt{(\omega^2 - p^2)^2 + 4b^2p^2}}sin(pt - tan^{-1}\frac{2bp}{\omega^2 - p^2})

First term represents the natural damped oscillation and the second term represents the forced oscillation. Initially both the vibrations will be present, but with the passage of time, the first term vanishes and the motion of the body will be completely represented by the second term.

So the solution is only,

x=f0(ω2p2)2+4b2p2sin(pttan12bpω2p2)x = \frac{f_0}{\sqrt{(\omega^2 - p^2)^2 + 4b^2p^2}}sin(pt - tan^{-1}\frac{2bp}{\omega^2 - p^2})

Case I: Low driving frequency

When (p<ω)(p < \omega), we have, A=f0(ω2p2)2+4b2p2A = \frac{f_0}{\sqrt{(\omega^2 - p^2)^2 + 4b^2p^2}}

On neglecting p2p^2, then A=f0ω2=F0/mω2A = \frac{f_0}{\omega^2} = \frac{F_0/m}{\omega^2} or A=F0mω2A = \frac{F_0}{m\omega^2}

Here, amplitude depends on force constant and mass.

For (p<ω)(p < \omega), Φ=tan1(0)=0\Phi = tan^{-1}(0) = 0

The force and displacement are always in phase.

Case II: High driving frequency

When (p>ω)(p > \omega), we have, A=f0(ω2p2)2+4b2p2A = \frac{f_0}{\sqrt{(\omega^2 - p^2)^2 + 4b^2p^2}}

On neglecting ω2\omega^2, then A=f0p4+4b2p2A = \frac{f_0}{\sqrt{p^4 + 4b^2p^2}}

Here, amplitude varies inversely with damping constant b and applied frequency p.

For (p>ω)(p > \omega), Φ=tan1(2bpp2)=2bp\Phi = tan^{-1}(\frac{-2bp}{p^2}) =\frac{-2b}{p}

if b is small, then 2bp=0\frac{2b}{p} = 0, so Φ=tan1(0)=π\Phi = tan^{-1}(0) = π

The displacement lags behind the force by a phase by π which means they are out of phase.

Case III : Resonance

Resonance is the condition where the applied frequency matches with the natural frequency.

There are two conditions for resonance:

  • The applied frequency pp should be equal to natural frequency ω\omega of a body.
  • The damping constant bb should be minimum.

When (p=ω)(p = \omega), we have, A=f0(ω2p2)2+4b2p2A = \frac{f_0}{\sqrt{(\omega^2 - p^2)^2 + 4b^2p^2}}

On putting ω=p\omega = p, then Amax=f04b2p2=F0/m4b2p2A_{max} = \frac{f_0}{\sqrt{4b^2p^2}} = \frac{F_0/m}{\sqrt{4b^2p^2}} or A=F02mbωA = \frac{F_0}{2mb\omega}

Here, amplitude varies inversely with damping force b. As damping force decreases, the amplitude of vibrating body increases. This leads to Resonance.

At resonance, the amplitude of oscillations is maximum. For small values of bb (low damping ), the amplitude decreases very rapidly on either side of the resonant frequency than for higher value of bb.

Also we know, τ=12b\tau = \frac{1}{2b}

  Amax=f0τω\therefore \; A_{max} = \frac{f_0 \tau}{\omega} , where τ\tau is relaxation time.

For (p=ω)(p = \omega), Φ=tan1(2bω0)=tan1()=π2\Phi = tan^{-1}(\frac{-2b\omega}{0}) = tan^{-1}(\infty) = \frac{π}{2}

The displacement lags behind the force by a phase by π2\frac{π}{2}.

Examples:-

  1. Swinging on a swing: Pushing a swing at its natural frequency amplifies its motion, demonstrating mechanical resonance.
  2. LC circuit: Resonance occurs in electrical circuits containing inductance and capacitance when the frequency of the applied alternating current matches the circuit's natural frequency.
  3. Guitar strings: Strings on musical instruments resonate when plucked or bowed at their natural frequencies, producing sound.
  4. Structural resonance in buildings: Vibrations from machinery or external forces can resonate with a building's natural frequency, leading to structural damage or collapse.
  5. Nuclear Magnetic Resonance (NMR): Nuclei in a magnetic field absorb and reemit electromagnetic radiation at their resonant frequencies, used in MRI machines and spectroscopy.

Sharpness of Resonance

The term sharpness of resonance refers to the rate of fall in amplitude with the change of driving frequency on either side of resonant frequency. Resonance is said to be sharp, when for a small change of the driving frequency from the resonant frequency, there is a large change in the energy of vibration.

When the damping is low, the amplitude falls of a very rapidly on either side of resonant frequency
and that the resonance is sharp. Example for sharp resonance is a sonometer wire with a tuning fork.

When the damping is high, the amplitude falls of very slowly on either side of resonant frequency and that the resonance is flat. Example for flat resonance is resonance of an air column.

When damping is zero, When damping is zero, theoretically, the amplitude of the system's oscillation would become infinite at the resonant frequency. However, in reality, there is always some form of damping present in physical systems, even if it is very small. This means that the amplitude cannot truly become infinite, although it may become extremely large if damping is negligibly small.

The figure shows the variation of amplitude with driving frequency.

Resonance

Sharpness of resonance is defined by the Q factor. Q measures sharpness of resonance. Quality factor at resonance is defined as the ratio of amplitude at resonance to the amplitude at zero driving frequency.

Q=AmaxAp=0=f0/2bωf0/ω2=ωτQ = \frac{A_{max}}{A_{p=0}} = \frac{f_0/2b\omega}{f_0/\omega^2} = \omega \tau, where τ\tau is 12b\frac{1}{2b} and is relaxation time.

How's article quality?

Last updated on -

Page Contents